Challenges for the sexual education of students with deeper intellectual disabilities in Poland - Kamecka-Antczak, Celina; Szafrański, Mateusz; Wos, Klaudia (Disability and education, 2023)
The article presents the results of participatory action research conducted with polish students with intellectual disability. The research concerned students’ knowledge of their own sexuality and their needs related to conducting sex education at a special school. The presented research is part of a larger project, which aimed to create a didactic tool for conducting sex education classes with people with intellectual disabilities. The research was conducted in accordance with the assumptions of the participatory paradigm, putting postulates being a response to the UN Convention of the Disabled Rights of Poland ratified by Poland.